Profil pasien refluks laringofaring di RSUP Prof. Dr. R. D. Kandou Manado - Runtung, Maureen; Pelealu , Olivia C. P.; Pontoh, Valentini M. (Universitas Sam Ratulangi, 2024)
Abstract: Diagnosis of laryngopharyngeal reflux (LPR) requires a clinical history based on clinical symptoms (Reflux Symptom Index - RSI) and laryngeal examination (Reflux Finding Score - RFS) due to its nonspecific symptoms and laryngoscopic signs do not always correlate with the severity of symptoms. This study aimed to obtain the profile of patients with LPR at Prof. Dr. R. D. Kandou Hospital. This was a retrospective and descriptive study using medical records of LPR patients at Prof. Dr. R. D. Kandou Hospital during the period 2020-2022. The results showed that the majority of LPR patients were females (57.6%), aged 41-65 years and occupation as housewife. The most commonly experienced complaints were difficulty in swallowing (36.3%) and feeling of throat tightness (25,0%). The most frequent endoscopic finding was erythema/hyperemia of the arytenoids (36.8%). In conclusion, laryngo-pharyngeal reflux is often experienced by females aged 41-65 years, occupation as housewife. The most common complaints are difficulty in swallowing and feeling of throat tightness. Erythema/hyperemia of the arytenoid has the highest percentage in endoscopic finding. Keywords: laryngopharyngeal reflux; patient profile Abstrak: Dalam mendiagnosis refluks laring faring (RLF), diperlukan anamnesis berdasarkan gejala klinis (Reflux Symptom Index - RSI) dan pemeriksaan laring (Reflux Finding Score - RFS) karena gejalanya tidak spesifik dan tanda laringoskopi tidak selalu sesuai dengan tingkat keparahan gejala. Penelitian ini bertujuan untuk mendapatkan profil pasien RLF di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif retrospektif menggunakan data pasien yang tercatat di Instalasi Rekam Medis RSUP Prof. Dr. R.D. Kandou Manado periode 2020 hingga 2022. Hasil penelitian mendapatkan bahwa mayoritas pasien RLF ialah perempuan (57,6%) dengan usia 41-65 tahun. Distribusi pekerjaan menunjukkan jumlah pasien tertinggi ialah ibu rumah tangga. Keluhan yang paling sering dialami ialah sulit menelan (36,3%) dan rasa mengganjal pada leher (25,0%). Temuan endoskopi paling sering ialah eritema/hiperemis aritenoid (36,8%). Simpulan penelitian ini ialah refluks laring faring sering dialami oleh perempuan pada usia 41-65 tahun, dengan pekerjaan sebagai ibu rumah tangga. Keluhan paling sering ialah sulit menelan dan rasa mengganjal di tenggorokan. Distribusi tertinggi pasien refluks laring faring berdasarkan kondisi laring ialah eritema/hiperemis aritenoid. Kata kunci: refluks laringofaring; profil pasien